Modularisation and outsourcing: who drives whom? A study of generational sequences in the US automotive cockpit industry. (6th June 2005) - Fixson, Sebastian K.; Ro, Young; Liker, Jeffrey K.
In this paper, we study the interactions between modularity and outsourcing in the auto industry. Focusing on vehicle cockpit projects in North America, we collect data over three product architecture generations and the associated shifts in firm boundaries for multiple processes covering product development and production. We find that the direction of influence between product architecture and firm boundary varies across individual processes and over time, resulting in a zig-zag path towards higher levels of modularity and outsourcing over the observed timeframe. The relative strength of the factors that drive these changes appears to be dependent on (a) idiosyncrasies of the logic of individual processes, i.e., their cost structure, their perceived strategic value, and the capabilities available in the supply chain for their completion, and on (b) the relevance and relative weight of external factors such as labour costs, capital cost, and external development of technologies.